Giant esophageal liposarcoma with squamous cell carcinoma resected via the cervical approach: a case report - Tomohiro Okura; Yasuhiro Shirakawa; Yuki Katsura; Takuya Yano; Michihiro Ishida; Daisuke Satoh; Yasuhiro Choda; Masanori Yoshimitsu; Nakano Kanyu; Hiroyoshi Matsukawa; Hitoshi Idani; Masazumi Okajima; et al. (Surgical Case Reports, 2022)
Abstract Background Liposarcoma is one of the most common soft tissue sarcomas, but is extremely rarely found in the esophagus. There have been no reports of esophageal liposarcoma together with superficial carcinoma of the esophagus. Here, we report a patient who underwent complete resection of esophageal liposarcoma with carcinoma via a cervical approach. Case presentation A 66-year-old man was diagnosed with an esophageal tumor 11 years ago, but he left it untreated. He presented to our hospital with progressive dysphagia and appetite loss since the previous year. Esophagogastroduodenoscopy (EGD) showed a large pedunculated submucosal tumor (SMT) originating at the esophageal entrance, extending to the gastroesophageal junction. Additionally, there was a superficial carcinoma on the surface of the SMT, 30 cm from the incisor teeth. Three-dimensional computed tomography (3D-CT) showed a giant elongated intraluminal tumor extending downwards from the cervical esophagus. We diagnosed a giant esophageal polyp accompanied by a superficial carcinoma and performed tumor resection via a cervical approach. The excised specimen consisted of a 23.0 × 8.5 cm polypoid mass. The final diagnosis by histopathological and immunohistochemical examination was well-differentiated liposarcoma and esophageal squamous cell carcinoma. He was discharged on postoperative day 14 with drastic improvement in his swallowing ability. Conclusion We reported an extremely rare case of esophageal liposarcoma together with esophageal squamous cell carcinoma that was successfully resected through a small cervical incision.